The role of collaborative networks in product-service system business models for an advanced manufacturing technology SME - Simões, J. R.; Vilas-Boas da Silva, J. M.; Duarte de Almeida, I. (22nd Cambridge International Manufacturing Symposium: Supply chain transformation enabled by advanced technologies, 2018)
This research appreciates the relevance of servitization business models for an Advanced Manufacturing Technology (AMT) SME in the Ornamental Stones (OS) cluster. A holistic conceptual model was designed and tested addressing strategy, organizational structure and technological infrastructure. Primary data gathered by semi-structured interviews were completed by unstructured observation and documentation studying. The model usefulness/usability was qualitatively confirmed by the outcomes relevance. As regards results, primary stages of servitization are already occurring in the case. They might progress towards advanced servitization, if both digital business platforms and Industry4.0 and collaborative networks are deployed. Moreover, the lack of open innovation in the OS SME generates strong feelings of ownership towards resources, which constrains servitization progress and provides a threat to cluster survival. However, a mandatory progress towards Building Information Modelling is expected, which is going to demand virtual breeding environments and virtual organizations that will leverage competitive advantage and enable servitization progress.